Reading About Multiethnicity - Wojdon, Joanna (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
This volume goes beyond its initial goal of transferring the findings of the research project on "Cohesion building of multiethnic societies in Europe in the 11th-21st c" into school practice. It is based on the concept of "reading like a historian" developed by Sam Wineburg at Stanford University. "Reading" includes not only traditional written sources, but also iconographic material, such as medieval miniatures, coats of arms, photographs, as well as family trees and maps. It provides easy-to-adapt ideas, questions and tools to move from superficial browsing to an in-depth critical analysis, taking into account the origin of the material, its historical context and confrontation with other documents and data.
Keywords: Agnes Wizla; historical maps; history education; history of Iberian Peninsula; panorama of Lviv; Muslims in Portugal; Chronica Hungarorum; Hungarian coat of arms; medieval miniatures; coat of arms; history of Hungary; history of Transylvania; Frederic Chopin portraits; family trees; Russian imperial coat of arms; history lessons; portraits of European kings; analysis of historical sources; history of Sardinia; Polish cathedral style; Jews in Portugal; inquiry-based historical learning; Saint Catharine; Polish churches in USA; history of Romania; Louis I of Hungary; historical thinking; multiethnic societies; Mariano IV of Sardinia; historical interpretation; primary and secondary sources; photography manipulation; European history; photography analysis; test of iron